Peaceful Settlement of International Disputes in the International Law and Islamic Law | التسوية السلمية للمنازعات الدولية في القانون الدولي والشريعة الإسلامية - Rahmat Adi Yulianto (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2014)
This study examines the resolution of conflicts between states based on the peacefulconcept, while the ways that based on violence and military force has been consideredby the international community as an illegal concept. The method of study is to compareand analyze the basic principles of resolution conflict based on peaceful that contained inthe international law and Islamic law. The result of research, it is known that resolutionof conflict which based on peaceful refer to how effectiveness of governance or goodgovernance, mediation, investigation, conciliation and other means.